Dielectric relaxation in a novel tapered chiral photochromatic liquid crystalline dendrimer. Issue 7 (27th May 2016) - Srivastava, Anoop Kumar; Kim, Dae-Yoon; Kim, Jongyoon; Jeong, Jinyoung; Lee, Ji-Hoon; Jeong, Kwang-Un; Singh, Vijay
ABSTRACT: Temperature-dependent dielectric spectroscopic measurements of newly synthesised ribbon-shaped chiral liquid crystalline dendrimer with photochromic azobenzene mesogens and an isosorbide chiral centre on planar anchoring cell have been performed in the frequency range of 1.0 Hz to 5.5 MHz. Three dielectric dispersions in the relaxation frequency range of 10–80 Hz, 80–130 kHz and 3.5 MHz have been observed not only in chiral smectic phase but also in isotropic phase in which two lower-frequency processes are retarded while the other one remained at same relaxation rate from isotropic to chiral smectic phase. Based on the dielectric and optical polarising microscopic results, the chiral smectic phase has been identified as SmC* phase. The relaxation mode observed at low-frequency region in the SmC* phase followed the dielectric characteristics of pinned Goldstone mode. Whereas the dielectric dispersions observed at high-frequency region have been analysed in the framework of the model given by Maier and Meier. GRAPHICAL ABSTRACT: